International human resource management - Brewster, Chris; Houldsworth, Elizabeth; Sparrow, Paul; Vernon, Guy (Chartered Institute of Personnel and Development, 2016)
"This fully updated 4th edition of International Human Resource Management includes extended coverage of cross-cultural management, a broader scope of countries and key topics such as global talent management, global leadership, global knowledge management, and differing national contexts. Filled with geographically diverse examples and case studies, and covering topics from culture and reward systems to managing expatriate assignment and diversity in international forms of working, it is an ideal textbook for all students of international HRM as well as HRM specialists and practicing managers"--Provided by publisher.